Out & About Athina Vahla's Wrestling and Angel - Roy, Sanjoy (Dance Books Ltd., Alton,Hampshire (UK), 2005)
Athina Vahla's Wrestling and Angel. PALABRAS CLAVE: Athina Vahla, Wrestling and Angel, abattoir, performance, Old Operating Theatre, outside the scenarios.
Dentro del apartado "Beyond the proscenium".